Cytogenetic tests reveal no toxicity in lymphocytes of rabbit (Oryctolagus cuniculus, 2n=44) feed in presence of verbascoside and/or lycopene. (April 2018) - Perucatti, Angela; Genualdo, Viviana; Pauciullo, Alfredo; Iorio, Ciro; Incarnato, Domenico; Rossetti, Cristina; Vizzarri, Francesco; Palazzo, Marisa; Casamassima, Donato; Iannuzzi, Leopoldo; Iannuzzi, Alessandra
Abstract: Phenylpropanoid glycosides (PPG), like other phenolic compounds, are a powerful antioxidants and the Verbascoside (VB) is one of the most active of them. A previous study, by using in vitro exposure of blood human lymphocytes to Verbascoside, reported a significant increasings of chromosome fragility compared to control. In the present study, four homogeneous groups of rabbits were used to test in vivo the VB and/or Lycopene (LP) by feeding the animals without VB and LP (control), in presence of VB or/and LP for 80 days. Lymphocyte cell cultures were performed in three different times: 0, 40 and 80 days of the experiment and the cytogenetic tests that we used [CA-test (Chromosome Abnormalities in terms of chromosome and chromatid breaks) and Sister Chromatid Exchange (SCE-test)] have revealed no mutagenic effects on chromosomes. Indeed, mean values/cell of CA and SCE decreased during the experiment with some difference among and within groups, with significant decreasing value only for some group. The study shows clear evidence that diets rich in Verbascoside (and/or Lycopene) do not originate any mutagenic activity, resulting no cytotoxic for the animals and, suggesting a possible their use in both animal and human diets.